2010
DOI: 10.1155/2010/638014
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Genesis and Progression: DNA Near-Diploid Aneuploidization and Endoreduplication by High Resolution Flow Cytometry

Abstract: Oral potentially malignant lesions (OPMLs) with dysplasia and aneuploidy are thought to have a high risk of progression into oral squamous cell carcinomas (OSCCs). Non-dysplastic “oral distant fields” (ODFs), characterized by clinically normal appearing mucosa sited at a distance from co-existing OPMLs, and non-dysplastic OPMLs may also represent an early pre-cancerous state. ODFs, OPMLs without and with dysplasia and OSCCs were investigated by high resolution DNA content flow cytometry (FCM). ODFs and OPMLs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Several groups have confirmed the value of DNA ploidy as a predictor of malignant transformation (Bradley et al, 2010;Bremmer et al, 2011;Siebers et al, 2013;Sperandio et al, 2013;Torres-Rendon et al, 2009;Zaini et al, 2018). Abnormal DNA ploidy correlates with the presence and severity of dysplasia (Donadini et al, 2010;Grässel-Pietrusky et al, 1982;Pentenero et al, 2009;Saito et al, ,1995Saito et al, , , 1998van Zyl et al, 2012), is more frequently found in higher grades of dysplasia (Li et al, 2020;Sperandio et al, 2013;van Zyl et al, 2012) and in lesions considered high-risk clinically (Xiao et al, 2015;van Zyl et al, 2012). Correlation with dysplasia is not necessarily an advantage since the predictive value of dysplasia is reported to be extremely variable, but DNA ploidy is able to detect changes in OPMD that have minimal or no dysplasia (Sperandio et al, 2013;Zaini et al, 2018), as can flow cytometry (Pentenero et al, 2012).…”
Section: Dna Aneuploidymentioning
confidence: 90%
See 2 more Smart Citations
“…Several groups have confirmed the value of DNA ploidy as a predictor of malignant transformation (Bradley et al, 2010;Bremmer et al, 2011;Siebers et al, 2013;Sperandio et al, 2013;Torres-Rendon et al, 2009;Zaini et al, 2018). Abnormal DNA ploidy correlates with the presence and severity of dysplasia (Donadini et al, 2010;Grässel-Pietrusky et al, 1982;Pentenero et al, 2009;Saito et al, ,1995Saito et al, , , 1998van Zyl et al, 2012), is more frequently found in higher grades of dysplasia (Li et al, 2020;Sperandio et al, 2013;van Zyl et al, 2012) and in lesions considered high-risk clinically (Xiao et al, 2015;van Zyl et al, 2012). Correlation with dysplasia is not necessarily an advantage since the predictive value of dysplasia is reported to be extremely variable, but DNA ploidy is able to detect changes in OPMD that have minimal or no dysplasia (Sperandio et al, 2013;Zaini et al, 2018), as can flow cytometry (Pentenero et al, 2012).…”
Section: Dna Aneuploidymentioning
confidence: 90%
“…A major advantage is the ability to use routine paraffin-embedded samples and select areas of interest after microscopic examination. The latest image-based systems can achieve 1% or less coefficient of variation in the diploid peak, providing a high sensitivity for the detection of aneuploid populations that should be equivalent to flow cytometry using high-resolution systems (Donadini et al, 2010).…”
Section: Dna Aneuploidymentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining features with the highest weight, and hence discriminating power, are at 1242 cm -1 and 1020 cm -1 : regions known to be dominated by contributions from DNA, RNA and glycogen [ 34 ]. Thus, a relatively high weighting of the IR data obtained at 1242 cm -1 might be indicative of an increase in DNA aneuploidy in T lesions compared with NT lesions, a known early event in oral carcinogenesis [ 36 , 37 ]. Similarly, the characteristic absorption peak of glycogen is centered at approximately 1030 cm -1 and its importance in the experiments presented in this report may correlate with the observation that abundance of the molecule is depleted in pre-malignant tissue as a result of increased proliferation requiring additional energy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on such evidence, a cost-effectiveness analysis from British Columbia showed that the use of a genomic assay to risk-stratify the management of low-grade dysplasia could not only lead to improved patient outcome, but also to a more rational allocation of resources(Cromwell et al 2016). Considering that hyperplastic and normal appearing mucosa have also been reported to undergo MT, it would also be beneficial to have more precise data on non-dysplastic lesions, which may represent the vast majority of OPMDs(Donadini et al 2010, Speight 2007). Of note, in the first study byMao et al…”
mentioning
confidence: 99%